Data for: Reconciling conservation and development requires enhanced integration and broader aims: A cross-continental assessment of landscape approaches. - Estrada Carmona, Natalia; Abigail, Hart; Zanzanaini, Camilla (2024)
This dataset describes 380 landscape approaches across three continents characterized with the same questionnaire. The data comes from three regional assessments Latin America and the Caribbean (Estrada-Carmona, Natalia, et al. 2014. “Integrated Landscape Management for Agriculture, Rural Livelihoods, and Ecosystem Conservation: An Assessment of Experience from Latin America and the Caribbean.” Landscape and Urban Planning 129:1–11); Africa (Milder, et al. 2014. “Integrated Landscape Initiatives for African Agriculture, Development, and Conservation: A Region-Wide Assessment.” World Development 54:68–80); and Asia (Zanzanaini, et al., 2017. “Integrated Landscape Initiatives for Agriculture , Livelihoods and Ecosystem Conservation : An Assessment of Experiences from South and Southeast Asia.” Landscape and Urban Planning 165:11–21). The dataset also includes a set of +23 landscape approaches characterized in 2021 through the CGIAR research network. The dataset includes two other tabs displaying the continuous and categorical variables significantly associated with each cluster of landscape approaches. Finally, the Metadata tab describes all the information provided in the dataset. (2024-03-18)